2020
DOI: 10.1002/cpp.2515
|View full text |Cite
|
Sign up to set email alerts
|

The impact on mental health practitioners of the death of a patient by suicide: A systematic review

Abstract: There is a growing body of research investigating the impact on mental health professionals of losing a patient through suicide. However, the nature and extent of the impact is unclear. This systematic review synthesizes both quantitative and qualitative studies in the area. The aim was to review the literature on the impact of losing a patient through suicide with respect to both personal and professional practice responses as well as the support received. A search of the major psychological and medical datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
97
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(109 citation statements)
references
References 71 publications
(221 reference statements)
10
97
0
2
Order By: Relevance
“…Fourth, the present review synthesized evidence on patient suicidal behavior including both attempted and death by suicide, which extends findings from previous reviews (e.g., Sandford et al, 2021). Our findings identified a gap in the empirical literature with only two studies (Leaune et al, 2021;Scupham & Goss, 2020) comparing the impact between death by suicide and attempted patient suicide.…”
Section: Future Directions For Researchsupporting
confidence: 82%
See 3 more Smart Citations
“…Fourth, the present review synthesized evidence on patient suicidal behavior including both attempted and death by suicide, which extends findings from previous reviews (e.g., Sandford et al, 2021). Our findings identified a gap in the empirical literature with only two studies (Leaune et al, 2021;Scupham & Goss, 2020) comparing the impact between death by suicide and attempted patient suicide.…”
Section: Future Directions For Researchsupporting
confidence: 82%
“…Previous studies have identified impacts of client suicidal behavior falling within the domains of personal and professional functioning (Leaune et al, 2019; Sandford et al, 2021; Séguin et al, 2014). Two comprehensive systematic reviews on this topic, conducted seven years apart, corroborated the professional and personal impact of patient suicidal behavior on mental health providers (Séguin et al, 2014; Sandford et al, 2021). Séguin and colleagues (2014) highlighted methodological drawbacks that required further addressing.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this unpredictability, clinicians often refuse to accept suicidal patients, refer those that become suicidal, or even terminate care with patients who attempt suicide after contractually agreeing not to do so (Linehan et al, 2012;Stanley & Brown, 2012). Many clinicians feel responsible for the lives of their patients and fear liability risks as well as the traumatizing impact of losing a patient to suicide (Linehan et al, 2012;Sandford et al, 2020), and find little comfort in a research on risk factors that oftentimes do not help in clinical decision-making (Burger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%